Military Supply of the Tactical Units of the Ukrainian National Self-Defense and UPA-West (Second Half of 1943 – Beginning of 1944). Theory and Practice - Drohobyts’kyy, Ihor (Narzędzia wojny, 2023)
The article will outline the state of provision of weapons and ammunition of the units of Ukrainian national self-defenses (UNS, UIA). The theoretical and ideological basis of this process will be characterized. The features of military support are described, which were determined by the actual state of deployment of the armed divisions of the national resistance movement. The analysis of the outlined topic will be carried out on the basis of a comparative approach based on relevant materials relating to the specifics of the military support of the main combatant forces of the theater of military operations in Galicia in the specified chronological period (UNS, AK, Soviet partisan units, etc.).